Husserl and the promise of time : subjectivity in transcendental phenomenology. - de Warren, Nicolas (New York : Cambridge university press, 2009)
Acknowledgements; Introduction: The promise of time: subjectivity in Husserl's transcendental phenomenology; 1. The ritual of clarification; 2. A rehearsal of difficulties; 3. The ghosts of Brentano; 4. The retention of time past; 5. The impossible puzzle; 6. The lives of others; 7. The life of consciousness; Appendix: note on textual sources; Bibliography.
Onderzoek KASK Professioneel (OFVP)
boek